Prevalence and Clinical Manifestations of Helicobacter Pylori with Reference to Histopathological Diagnosis - Makaju, R; Dhakal, B.; Dhakal, R. (Kathmandu University Medical Journal, 2020)
Background Helicobacter pylori infection is on a steep decline in most of the developed countries; however, in developing countries like Nepal such steep decline is not seen. This may be due to failure of treatment regimens and emergence of drug resistance. Our previous study done in 2004/2005 showed 38% prevalence of Helicobacter pylori. The present study has been conducted to review the prevalence and clinical diagnosis of Helicobacter pylori with reference to histo-pathological diagnosis.Method This was retrospective study done at Dhulikhel Hospital, Kathmandu University Hospital over a period of 13 years from January 2006 to December 2018. Helicobacter pylori proven cases were retrospectively analyzed with clinical features and endoscopy findings. The clinical picture were categorized into antral gastritis, gastroduodenits, erosive duodenitis, acid peptic disease, reflux esophagitis, hiatal hernia, polyp, ulcer (gastric and duodenal), acute abdomen, upper gastrointestinal bleeding and malignancy.Result A total of 1624 upper gastrointestinal endoscopy biopsies were taken during the study period. Helicobacter pylori infection was seen in 618 (38.0%) cases out of 1624 cases. Helicobacter pylori were seen in 349 male and 269 female patients with male to female ratio of 1.29:1. Clinically, gastritis 210 (41.4%), acid peptic disease74 (42.7%), gastroduodenitis 46 (37.7%), reflux esophagitis 38 (52.7%), gastric ulcer 48 (28.4%), duodenal ulcer 34 (53.1%) and acute abdomen 50 (42.3%) cases were seen respectively.Conclusion Most commonly Helicobacter pylori cause chronic gastritis in our context. There is no significant change in prevalence of Helicobacter pylori infection as compared to our previous study (2004/05). This needs proper management of Helicobacter pylori infection to prevent serious complication such as gastric cancer in our part of the world.